Evaluation of hot mix asphalt mixtures containing reclaimed asphalt pavement and crumb rubber - Nor Shahadah, Hassan (2019)
In recent years, crumb rubber (CR) has been applied widely in asphalt pavement. Many researchers have indicated that crumb rubber (CR) asphalt mixture is an environmentally friendly material and Reclaimed Asphalt Pavement (RAP) is old asphalt pavement that has been removed from a road by milling or full depth removal. The use of RAP in hot mix asphalt (HMA) eliminates the need to dispose old asphalt pavements and conserves asphalt binders and aggregates, resulting in significant cost savings and benefits to society. This paper presents a study on HMA with different RAP mix and crumb rubber proportions carried out to evaluate the mechanical properties and performance of asphalt mixes containing RAP different proportions of crumb rubber. Marshall Mix Design Method was used to produce control mix and asphalt mixes containing 40% RAP, 40% RAP 2% CR and 40% RAP 6% CR in accordance with Specifications for Road Works of Public Works Department, Malaysia (JKR/SPJ/2008) for AC14 dense graded asphalt gradation and parameter Marshall test. Marshall stability and flow test was analysis performed to ensure that the result is compliance with specification requirements. The resilient modulus test was performed to measure recoverable strain of the material under repeated stress without reaching the failure limit. The dynamic creep test was performed to measure the rutting potential of the asphalt mixture. The results obtained showed that there was no substantial difference in Marshall stability and flow test and resilient modulus between asphalt mixes with RAP40, RAP40CR2, RAP40CR6 and the control mix. The test results indicated that recycled mixes performed as good as the performance of conventional HMA in terms of Marshall Stability, flow test and resilient modulus.